2004
DOI: 10.5713/ajas.2004.394
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Essential Oil Components on Growth Performance and the Functional Activity of the Pancreas and Small Intestine in Broiler Chickens

Abstract: To investigate the efficacy of alternatives to antibiotics, the present study was conducted to compare the effects of antibiotic, lactic acid, a blend of commercial essential oils (EOs) and EOs in combination with lactic acid on growth performance and the functional activity of the gut in broiler chickens. A total of 168 broiler chickens were given the basal diet supplemented with 10 ppm colistin (T1), 0.1% lactic acid (T2), 25 ppm EOs (T3), 25 ppm EOs+0.1% lactic acid (T4), 50 ppm EOs (T5) or 50 ppm EOs+0.1% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 21 publications
7
94
0
Order By: Relevance
“…Feed conversion ratio was numerically improved at 0.6% thyme extract group in both starter, grower and over the whole trial period compared to other treatment, but the different was not significant. These results are in agreement with previous studies in broilers (Lee et al, 2003a;Jang et al, 2004;Abdolkarimi et al, 2011). In different studies conducted to evaluate the effect of thyme on broiler performance, inconsistent results have been obtained.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Feed conversion ratio was numerically improved at 0.6% thyme extract group in both starter, grower and over the whole trial period compared to other treatment, but the different was not significant. These results are in agreement with previous studies in broilers (Lee et al, 2003a;Jang et al, 2004;Abdolkarimi et al, 2011). In different studies conducted to evaluate the effect of thyme on broiler performance, inconsistent results have been obtained.…”
Section: Resultssupporting
confidence: 94%
“…Growth promoting agents may have more impact when the diet in use is less digestible. In addition, it is know that well-nourished, healthy chicks do not respond to antibiotic supplements provided that they are housed under clean and disinfected conditions (Jang et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the addition of CA to diets should promote growth. This was also found by Jang et al (2004) who reported that a blend of organic acid with essential oils showed increase in pancreatic and intestinal mucosa digestive enzyme activities, resulting an increase in growth. Moreover, downfall in pH caused reduction in GI tract digesta transmission speed that was justifiable by resulting in reduction of FI in diets having 6% CA.…”
Section: Discussionsupporting
confidence: 63%
“…The use of phytogenics as feed additives is gaining importance due to their antimicrobial and stimulatory effects on digestive system ( Jamroz et al, 2003;Jang et al, 2004). They include herbs, spices or plants that are used to keep the gut microflora of poultry normal, which is a prerequisite for cost efficient and ecofriendly poultry production (Windisch and Kroismayr, 2006).…”
Section: Introductionmentioning
confidence: 99%